US-Cuban relations : from the cold war to the colder war. - DOMINGUEZ, Jorge I. (1997)
Presents four explanations for the high confrontation and impasse in US-Cuban relations, viz. (1) the distribution of power in the international system with the end of the Cold War; (2) ideological themes of both US and Cuban policies; (3) the role of domestic politics; and, (4) the 'balance' provided by other international governments which have deterred the US from adopting more aggressive policies.